Transfers and taxes as instruments of redistribution - Piotrowska, Maria (Publishing House of the Wrocław University of Economics, 2009)
The purposes of the paper are as follows: (1) to discuss the usefulness of trans-fers and taxes in lowering income inequality; (2) to appraise the efficiency of transfers and taxes in Poland, and (3) to evaluate trade-offs between redistributive instruments in terms of their impact on income inequality and budget expenditure in Poland. The empirical research is based on the method of analysing the effect of small changes in income sources on the inequality of income distribution [Lerman, Yitzhaki 1994]. The data come from the 2006 Family Budget Surveys (FBS) of Poland.. (fragment tekstu)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 59, s. 370-378